Ethics, issues and challenges in quality global Online Distance Higher Education provision - Nicolaides, Angelo; Onumah, Joseph Mensah (West African Journal of Open and Flexible Learning, 2017)
The quest for quality in the learning process in Open Distance Higher Education (ODeL) is enduring and it is hopefully persistently leading to better ways which would enable quality learning to take place. It is apparent that many distance education institutions are moving from a purely print-based to an online delivery approach through the use of virtual learning environments (VLEs) and by making use of numerous technological innovations. Academic institutions are challenged to prepare graduates to compete ethically in the 21st Century knowledge economy. In some ways however, technology is somewhat of a disruptive innovation. This paper discusses the issues and challenges that online distance higher education (ODeL) poses and discusses strategies which could possibly be employed by institutions to diminish unethical practices and further suggests some reasons why students choose to be dishonest in the digital era. It is clear that policy development and administrative changes are required to support innovative teaching practices across an institution. Distance education (DE) is also progressively global, with universities leveraging cutting 22 West African Journal of Open & Flexible Learning Volume 5, Number 2, January 2017 edge technologies to place education within the grasp of many more individuals and this requires additional skills. Suggestions are also proffered as to what academics can do to mitigate unethical academic practices. In this regard, a carefully crafted moral education approach and well-conceived course design are needed to construct a sound academic culture and promote the desired levels of integrity. The core issue is how unethical student practices can be eliminated where the use of information technology is required in all teaching and learning. The findings and conclusions may be relevant for other institutions in the ODeL arena. Résumé : La recherche de l’assurance de qualité dans le processus de l’enseignement supérieur à distance (ESD) est une quête durable qui permettrait de réaliser une meilleure façon d’apprentissage. Il est évident que de nombreux établissements d’enseignement à distance sont en train de passer d’une approche purement imprimée à une approche numérique, grâce à l’utilisation d’environnements d’apprentissage virtuels (EAV) et à l’utilisation de nombreuses innovations technologiques. Les établissements d’enseignement sont mis au défi de préparer les diplômés à être compétitifs sur le plan éthique dans l’économie du savoir du XXIe siècle. Dans quelques mesures, la technologie est en quelque sorte une innovation perturbatrice. Cette communication examine les problèmes et les défis que pose l’enseignement supérieur à distance numérique (ODeL) et examine les stratégies qui pourraient être utilisées par les établissements pour réduire les pratiques contraires à l’éthique et suggère quelques raisons pour lesquelles les étudiants choisissent d’être malhonnêtes à l’ère numérique. Il est clair que les changements politiques et administratifs sont nécessaires pour appuyer les pratiques d’enseignement novatrices dans l’ensemble d’un établissement. L’enseignement à distance est également de plus en plus mondial, les universités tirant parti des technologies de pointe pour mettre l’éducation à la portée d’un plus grand nombre d’individus, ce qui exige des compétences supplémentaires. Des suggestions sont également avancées quant à ce que les universitaires peuvent faire pour atténuer les pratiques académiques contraires à l’éthique. Cet égard, une approche soigneusement conçue de l’éducation morale et des matérielles d’études bien conçue sont nécessaires pour construire une culture académique solide et promouvoir les niveaux d’intégrité souhaités. La question centrale est de savoir comment éliminer les pratiques contraires à l’éthique des étudiants lorsque l’utilisation des technologies de l’information est nécessaire dans tout l’enseignement et l’apprentissage. Les résultats et les conclusions de la communication peuvent être pertinents pour d’autres institutions de l’ODeL.